A molecular dynamics study on iridium - Ferah, Gulen; Colakoglu, Kemal; Ciftci, Yasemin Oztekin; Ozgen, Soner; Kazanc, Sefa (De Gruyter Poland Sp Zoo, 2007)
In this study, molecular dynamics simulations are performed by using a modified form of Morse potential function in the framework of the Embedded Atom Method (EAM). Temperature-and pressure-dependent behaviours of bulk modulus, second-order elastic constants (SOEC), and the linear-thermal expansion coefficient is calculated and compared with the available experimental data. The melting temperature is estimated from 3 different plots. The obtained results are in agreement with the available experimental findings for iridium. (c) Versita Warsaw and Springer-Verlag Berlin Heidelberg. All rights reserved.
Keywords: molecular dynamics simulation; embedded atom method; phase diagrams; elastic constants